Psychosocial sequelae of stoma surgery for inflammatory bowel disease in childhood. Issue 10 (October 1987) - Lask, B; Jenkins, J; Nabarro, L; Booth, I
Abstract : Three matched groups of children with inflammatory bowel disease: (a) stroma group, (b) ileorectal anastomosis group and (c) no-surgery group were compared for psychosocial adjustment. No differences were found between the groups for psychological adjustment, selfesteem, or quality of life. It is concluded that providing children are well prepared and followed up carefully and sensitively, then stroma surgery should not be deferred for fear of adverse psychological consequences.